Gas transport mechanisms during high-frequency ventilation - Thomas J. A. Scott; Chinthaka Jacob; David G. Tingay; Justin S. Leontini (Respiratory Research)
Abstract By virtue of applying small tidal volumes, high-frequency ventilation is advocated as a method of minimizing ventilator-induced lung injury. Lung protective benefits are established in infants, but not in other patient cohorts. Efforts to improve and extend the lung protection potential should consider how fundamental modes of gas transport can be exploited to minimize harmful tidal volumes while maintaining or improving ventilation. This research investigates different models of gas transport during high-frequency ventilation and discusses the extent to which the gas transport mechanisms are considered in each. The research focuses on the rationale for current ventilation protocols, how they were informed by these models, and investigates alternative protocols that may improve gas transport and lung protection. A review of high-frequency ventilation physiology and fluid mechanics literature was performed, and dimensional analyses were conducted showing the relationship between clinical data and the model outputs. We show that contemporary protocols have been informed by resistor-inductor-capacitor, or network, models of the airway-lung system that are formulated around a ventilation pressure cost framework. This framework leads to clinical protocol selection that ventilates patients at frequencies that excite a resonance in the lung. We extend on these models by considering frequencies that are much higher than resonance which further optimize gas transport in the airway via alternative gas transport mechanisms to bulk advection that operate for very low tidal volumes. Our findings suggest it is unlikely that gas transport is optimally exploited during current approaches to high-frequency ventilation and protocols that differ significantly from those currently in use could achieve ventilation while using very low tidal volumes.